The effects of a community mental health intervention project upon family caregivers of persons with suspected mental illness in the Chinese cultural context. (November 2018) - Ng, Petrus; Young, Daniel KW; Pan, Jiayan; Law, King-Keung
Family members play an important role in caregiving with more emphasis on early intervention for people suffering from mental illness. Using both quantitative and qualitative methods, this study examines the effects of a community mental health intervention project (CoMHIP) on burdens of caregivers who have family members with suspected mental illness. Results showed that family caregivers' burden and psychological stress level had been reduced ( p < .001). The caregivers subjectively experienced a significant reduction in stress regarding the caregiving subscales, supervision, tension, worrying and urging after seeking CoMHIP service. Findings for the study have implications on social work interventions regarding family caregiving of people with suspected mental health problems.